Bom Jesus do Piauí and its fluctuations in the thermal sensation (Research, Society and Development, 2021)
Atmospheric conditions and adverse effects on regional and local climate have a strong influence on society and have been causing bioclimatic stress conditions that affect health and human condition. The objective is to evaluate and spatially analyze the variability of the thermal sensation and its level of discomfort relating the behavior of the climate and the urban configuration for the municipality of Bom Jesus Piauí. Monthly and annual data of maximum and minimum average temperature and relative humidity in the period from 1960 to 2018, from the meteorological station of the National Institute of Meteorology, located in the studied area, were used. The Thom discomfort index was applied in order to detect the possible variability of climate trend observed in the referred elements studied, at a local scale. It was evident that in the early mornings the temperature has been warmer and with a stifling sensation, while in the afternoons the thermal fluctuations remain stationary. It was also found that the increase in air temperature is due to the strong fluctuation of the tendency to increase the minimum air temperature.